Large devaluations and inflation inequality: Evidence from Brazil - Raphael Rocha Gouvêa (University of Massachusetts, Department of Economics, 2020)
In the aftermath of large devaluations, prices of tradable goods/lower-priced varieties increase significantly more than the prices of nontradables/higher-priced varieties. These relative price changes may lead to inflation inequality when household consumption baskets are different across the distribution of income. Using Cravino and Levchenko [2017]'s methodology, we show that inflation of poor households in Brazil was at least 11 percentage points higher than of the rich in the aftermath of the 2002 large devaluation. A detailed case study of the City of S\~ao Paulo estimates an inflation inequality ranging from 8 to 11 percentage points in the city.
Keywords: F31; F41; E31; 330; Exchange Rate Devaluation; Pass-Through; Inflation; Inequality